Dampak Peningkatan Kepuasan Pelanggan dalam Proses Bisnis E-Commerce pada Perusahaan Amazon.Com - Karmawan, I Gusti Made (Bina Nusantara University, 2014)
The Purpose of writing is to describe the impact of increased customer satisfaction in the business process of e-commerce at Amazon.com and analyzed e-commerce strategies used in the company.The Benefits are to get an overview of the strategies in the Amazon.com for improving customer satisfaction and the impact of increased satisfaction. The method of writing is conducting reviews of existing sources to gain an overview strategy and business processes e-commerce at Amazon.com. The paper results are gaining knowledge of thenumber of visitors and Sales that accurred at Amazon.com. The Conclusions is about the impact of increasing customer Satisfaction in the business process e-commerce in the Amazone.com.